Accumulation of long-chain unsaturated fatty acids in the airway inflammatory microenvironment drives eosinophil etosis and corticosteroid resistance - Yurong Bai; Pengda Fang; Shasha Li; Zhenhao Xiao; Wenyi Chen; Wenlong Li; Xinyue Wang; Jingyuan Chen; Yue Li; Junhai Chen; Weiqiang Huang; Xin Luo; et al. (Cell Communication and Signaling)
Abstract Background Eosinophilic inflammation is a feature of chronic rhinosinusitis with nasal polyps (CRSwNP). Patients with eosinophilic CRSwNP (ENP) tend to be refractory and prone to recurrence. Although there is increasing evidence linking lipid metabolic irregularities to eosinophilia, the particular lipid responsible for promoting eosinophilic inflammation and the precise molecular mechanisms involved remain unclear. Methods Lipidomic atlas and metabolic pathway enrichment were identified by liquid chromatography-tandem mass spectrometry and RNA sequencing, respectively. Eosinophil extracellular trap cell death (EETosis) was detected by immunofluorescence microscopy and transmission electron microscopy. Functional analyses were performed on purified eosinophils. Results The unbiased lipidomic atlas identified a specific accumulation in long-chain fatty acids (LCFAs) in ENP. Consistently, RNA-seq analysis confirmed the enrichment in long-chain unsaturated fatty acid metabolism pathway in ENP. In this lipid-rich airway inflammatory environment, EETosis including ETotic eosinophils, EETs release and Charcot-Leyden crystals (CLCs) generation was enhanced in ENP, and associated with disease severity. Further, we found that both saturated and unsaturated LCFAs, such as arachidonic acid, are critical fuel sources to trigger eosinophil activation and filamentous DNA release, whereas only arachidonic acid could induce crystalline Galectin10 (CLCs). Mechanistically, arachidonic acid induces EETosis through a mechanism independent of reactive oxygen species but the IRE1α/XBP1s/PAD4 pathway. Both the long-acting dexamethasone and short-acting hydrocortisone, while facilitate eosinophil apoptosis, are ineffective to block arachidonic acid-induced EETosis. Conclusions Our findings demonstrate a previously unknown role of the LCFA arachidonic acid in mediating EETosis and glucocorticoid insensitivity to drive ENP progression, which may lead to novel insights regarding the treatment of patients with refractory eosinophilic inflammation.